Pentingnya Etika Bisnis Dalam Menjaga Hubungan Dengan Konsumen - Nurhalima, Rusty Aliya (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to analyze the importance of the role of business ethics in maintaining mutually beneficial relationships between companies and consumers. In an increasingly competitive business environment, the implementation of sound ethics can be a determining factor in building and maintaining consumer trust. This research employs a literature review method by examining various references, including books, journal articles, and relevant previous studies. Through this analysis, the study focuses on key concepts of business ethics, such as transparency, honesty, and corporate social responsibility, and their application in the relationship between companies and consumers. The results indicate that companies that effectively implement business ethics are able to build stronger trust among consumers, which in turn enhances loyalty and increases customer retention. In addition, business ethics play a significant role in managing corporate reputation, as consumers tend to prefer brands they perceive as responsible and attentive to their well-being. Companies committed to ethical practices are also more responsive to consumer feedback and complaints, which helps improve their products and services. Furthermore, consistent application of business ethics enables companies to face crises with integrity and find fair solutions, thereby reducing the risk of losing consumer trust. The study also reveals that companies that implement corporate social responsibility (CSR) effectively, particularly in social and environmental aspects, can foster deeper and more positive relationships with consumers. Overall, this study demonstrates that business ethics are not merely moral principles, but also a crucial strategy for strengthening long-term consumer relationships and enhancing a company’s competitive position in the market.